Population growth of a generational cohort of the copepod Apocyclops panamensis (Marsh, 1913) under different temperatures and salinities - Cruz-Rosado, Leonardo; Contreras-Sánchez, Wilfrido Miguel; Hernández-Vidal, Ulises; Perez-Urbiola, Juan Carlos; Contreras-García, María de Jesús (Ecosistemas y Recursos Agropecuarios, 2020)
This study was carried out to identify the effects of salinity and temperature during Apocyclops panamensis culture, fed with Tetraselmis chuii. The experiment was conducted in laboratory conditions for 14 days. Nauplii from the same cohort were used to start the experiment, using a density of 1 ind mL−1 in a volume of 400 mL. The feed consisted of a daily supply of 20 000 cell mL−1 of microalgae. Nine treatments with three replicates were evaluated (24◦C-28h, 24◦C-32h, 24◦C-36h, 28◦C-28h, 28◦C-32h, 28◦C-36h, 32◦C-28h, 32◦C- 32h and 32◦C-36h). The factorial ANOVA indicates that temperature had a significant effect on the abundance of total copepods at day 14 (p = 0.02), while salinity did not show a significant effect (p = 0.06) on the total population of A. panamensis. Significant effects of temperature (p < 0.01) and salinity (p < 0.001) were observed for the nauplii population. The best growth of the entire population was reached in the treatment 32◦C-28h, with a population of 1 380.95 (± 1 267.06 ind L−1 (± 1 267.06) at the end of the experiment. Treatments 32◦C-28h and 32◦C-32h produced the highest average population of nauplii and copepodites at the end of the experiment. Adult females presented the greatest abundance in the 32◦C-32h treatment with 214.29 ind L−1, adult males increased between days 11 and 14 in treatments 24◦C-28h, 32◦C-28h, and 32◦C-32h without exceeding 170 ind L−1. In this study, it is evident that A. panamensis prefers warm temperatures and brackish environments.
Keywords: Apocyclops panamensis; Salinity; Temperature; Copepod culture